Mining of the Association Rules Between Socio-Economic Development Indicators and Rural Harmless Sanitary Toilet Penetration Rate to Inform Sanitation Improvement in China - Li, Yong; Cheng, Shikun; Cui, Jiangshui; Gao, Mingjun; Li, Zifu; Wang, Ling; Chen, Cong; Basandorj, Davaa; Li, Tianxin (Frontiers in Environmental Science, 2022)
The imbalance of socio-economic development (SED) in different regions of China has resulted in the variability of rural infrastructure penetration. This study aims to improve the SED of each region in China for increasing the penetration rate of rural harmless sanitary toilets (RHST). For this purpose, we used association rule mining to analyze the relationship between SED indicators and the penetration rate of RHST for proposing differentiated improvement strategies. Population urbanization rate, tertiary vs. secondary industry output ratio, nonagricultural output value ratio, nonagricultural employment ratio, per capita gross domestic product, and the proportion of added value of industry in the total added value of commodity were used to measure the SED level of 30 regions in China from 2007 to 2017. Results showed that the SED of each region has been improving, and the proportion of added value of industry in the total added value of commodity accounted for the highest proportion of SED. The penetration rate of RHST in each region increased continuously but with significant variability from 2007 to 2017. The range of six SED indicators corresponding to high and low penetration rates of RHST was determined by association rule mining analysis. On the basis of the degree of RHST penetration rate by region in China in 2017 as a reference, differentiated measures were proposed to improve the penetration of RHST in different regions.